2020
DOI: 10.1101/2020.07.17.209361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A framework for studying behavioral evolution by reconstructing ancestral repertoires

Abstract: Although extensive behavioral changes often exist between closely related animal species, our understanding of the genetic basis underlying the evolution of behavior has remained limited. Here, we propose a new framework to study behavioral evolution by computational estimation of ancestral behavioral repertoires. We measured the behaviors of individuals from six species of fruit flies using unsupervised techniques and identified suites of stereotyped movements exhibited by each species. We then fit a Generali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 48 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…While the complexity of the behavioral repertoire remains unchanged, the complexity of how the animals traverse through this space over time might still show significant deviations. Prior investigations into the complexity of fly behavioral sequences have shown that these dynamics of transitions between stereotyped behaviors exhibit long time scales and hierarchical organization [18,24]. A hypothesis for aging-related behavioral change is that the structure of the behavioral repertoire becomes less complex with age [25,26], and with the detailed measurements of behavior described here, we can test this idea, potentially gaining insight into changes occurring to the internal programs that may generate these patterns.…”
Section: Long Time Scales and Hierarchical Structure In Behavior With Agementioning
confidence: 74%
See 2 more Smart Citations
“…While the complexity of the behavioral repertoire remains unchanged, the complexity of how the animals traverse through this space over time might still show significant deviations. Prior investigations into the complexity of fly behavioral sequences have shown that these dynamics of transitions between stereotyped behaviors exhibit long time scales and hierarchical organization [18,24]. A hypothesis for aging-related behavioral change is that the structure of the behavioral repertoire becomes less complex with age [25,26], and with the detailed measurements of behavior described here, we can test this idea, potentially gaining insight into changes occurring to the internal programs that may generate these patterns.…”
Section: Long Time Scales and Hierarchical Structure In Behavior With Agementioning
confidence: 74%
“…The results of this calculation for each individual animal are shown in Figure 4B as a function of age. While there is significant scatter in the data (likely due to variance in the internal activity state of the flies [18,24]), when we compute a smoothed average of the data, a clearer portrait emerges. Specifically, we observe that these curves are reminiscent of the sexual dimorphism we observed in the inter-group eigenvector projections in Figure 3.…”
Section: Estimated Energy Consumption Alters With Agementioning
confidence: 99%
See 1 more Smart Citation
“…A recent investigation of unstimulated behaviors in different Drosophila species detected differences in spontaneous grooming between species and among individuals within a species (31). Using similar methods, they accurately assigned individuals into species categories and assessed variability among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors have been implicated in spontaneous (i.e., unstimulated) grooming behavior in Drosophila melanogaster (36) and in other drosophilid species (31). Our results demonstrate that this is true for dust-induced grooming as well.…”
Section: Discussionmentioning
confidence: 99%